Injection characteristics and fuel-air mixing process of ammonia jets in a constant volume vessel. (15th November 2021) - Zhang, Zhifei; Li, Tie; Chen, Run; Wang, Ning; Wei, Yijie; Wu, Dawei
Highlights: A three-stage behavior of tip penetration in ammonia jets are proposed. The ammonia and methane jets have similar S, α and fuel mole fractions at jet axis. The hyperbolic decays of fuel concentrations at the jet axis are confirmed. Fuel concentrations in ammonia jet increase with increased Pinj but reduce with Pa . Ammonia and methane jets show distinct flammable mixture distributions. Abstract: The direct-injection of gaseous ammonia is a possible way to fuel engines to meet the scenario of zero-carbon emission. In this study, for the first time, the injection characteristics and fuel–air mixing process of ammonia jets are investigated. A Schlieren system is employed to characterize the macroscopic behavior of ammonia jets including the tip penetration and jet angle. Besides, the fuel concentrations of ammonia jets are quantitatively measured by LIBS to investigate the fuel–air mixing processes. According to the time evolutions of jet tip penetration, the three-stage behavior, namely the t, t 0.5 and (t-τ) 0.25 dependence corresponding to the early stage of injection, quasi-steady stage and after two times of injection duration respectively, are proposed and the mechanisms are discussed in detail. The effects of both injection and ambient pressures on the tip penetration and jet angle, as well as the fuel concentration distributions are investigated. The increased injection pressure leads to increases in the tip penetration and fuel concentration but decreases in the jet angle. The effects of ambient pressure are opposite, indicating that the ammonia jet development is governed by the injection-to-ambient pressure ratio. The comparisons between ammonia and methane jets are conducted. The results show they have quite similar tip penetrations and jet angles, as well as the nearly equivalent fuel mole fractions at the jet axis. However, the equivalence ratios in ammonia jets are significantly lower than those in methane jets, leading to the distinct flammable mixture distributions in ammonia and methane jets.